2005
DOI: 10.1016/j.polymer.2005.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Strain amplitude response and the microstructure of PA/clay nanocomposites

Abstract: Abstract:PAn nanocomposites with various clay loadings were prepared by melt compounding in a twin extruder. Exfoliation of clay in a PA matrix was confirmed by X-ray

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 21 publications
(13 reference statements)
4
20
0
1
Order By: Relevance
“…This overshoot reaches a maximum at shear strains of 5-10 % and is followed by shear thinning behaviour at even larger strains. Similar overshoots were previously observed in polyamide-6 clay nanocomposites (Wan et al 2005) and have been attributed to and can be modelled by the different amplitude dependence of the rate Fig. 1 Amplitude sweeps of normalised storage modulus G /G 0.5 % and loss modulus G /G 0.5 % measured at 2π rad s −1 of (a) unfilled PC 2205 at temperatures 160-260 • C and of (b) PC-MWCNT (3 wt%) 2205 at temperatures 160-300 • C. The vertical dashed line indicates the linear viscoelastic limit of cluster formation relative to that of cluster destruction (Hyun et al 2011).…”
Section: Resultssupporting
confidence: 88%
“…This overshoot reaches a maximum at shear strains of 5-10 % and is followed by shear thinning behaviour at even larger strains. Similar overshoots were previously observed in polyamide-6 clay nanocomposites (Wan et al 2005) and have been attributed to and can be modelled by the different amplitude dependence of the rate Fig. 1 Amplitude sweeps of normalised storage modulus G /G 0.5 % and loss modulus G /G 0.5 % measured at 2π rad s −1 of (a) unfilled PC 2205 at temperatures 160-260 • C and of (b) PC-MWCNT (3 wt%) 2205 at temperatures 160-300 • C. The vertical dashed line indicates the linear viscoelastic limit of cluster formation relative to that of cluster destruction (Hyun et al 2011).…”
Section: Resultssupporting
confidence: 88%
“…As expected, the maximum strain to which the linear viscoelastic domain extends was observed to be decreasing while increasing the clay concentration [86]. Aubry et al [87] first observed g c ff À1 in polyamide-12 layered silicate.…”
Section: Clay Nanocompositessupporting
confidence: 62%
“…The region of linear viscoelastic behaviour for the matrix extends up to 40% strain, but falls down to lower than 1% when whiskers are added to nanocomposites prepared with 0 and 1% MPS. It is worth noting that non-linear viscoelastic behaviour is often observed in the case of polymeric matrix reinforced by nanofillers such as clay [24], fumed silica [25], carbon nanotubes [26] and so on. A number of different local mechanisms related to the change in network structure have been proposed to explain this phenomenon [27].…”
Section: Strain Amplitude Response Of the Nanocomposite In The Melt Smentioning
confidence: 99%